Keeping the family close: A fresh look at P.Oxy. 2459 (Euripides, Oedipus) - Prodi, EE (Dr. Rudolf Habelt, 2022)
P.Oxy. XXVII 2459, held at the British Library, comes from a papyrus roll of Euripides’ Oedipus assigned to the fourth century AD.1 It was fi rst published by E. G. Turner as fi ve separate fragments (now E. frr. 540– 540b Kannicht). The attribution was based upon the fi rst of the fi ve, which overlapped with a known quotation (vv. 1–2) and with an adespoton (vv. 7–9).2 Scholars who have studied the papyrus since its fi rst publication – my earlier self included – have tended to do so more with an eye to literary interpretation or textual improvement than to gaining a better sense of these remains on the material level.3 Yet a fresh inspection of the original with a resolutely papyrological focus yields interesting results, with important consequences for the text in turn. The present article offers (I) my arguments on the relative position of Turner’s frr. 1–5; (II) a new critical text of the fragment (now emphatically singular); and (III) selected textual notes.